PERANCANGAN LABORATORIUM PADA CAMPURAN ASPHALTIC CONCRETE BINDER COURSE (AC-BC) DENGAN ABU SERBUK BUNGKIL BIJI POHON JARAK PAGAR SEBAGAI FILLER - , MARHADI SASTRA, Ir. Latif Budi Suparma, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
With the increasing of the transportation mobility that occurs at this time there needs an innovation in the design of road pavement to create a good road conditions. In general, the aggregate for road pavement that are used is crushed stone, sand and stone dust as a filler. in this time to obtain of stone dust is difficult, so it needs an alternative for filler. With this condition, the jatropha oilcake ash which untapped expected with optimum can be used to an alternative of filler, especially in AC-Binder course mixture. In this research was conducted with 5 variations of the filler, they are variation 1 (100% stone dust + 0% jatropha oilcake ash), variation 2 (75% stone dust + 25% jatropha oilcake ash), variation 3 (50 % stone dust + 50% jatropha oilcake ash), variation of 4 (25% stone dust + 75% jatropha oilcake ash), variation 5 (0% stone dust + 100% jatropha oilcake ash). Having obtained the optimum bitumen content of each variation is then performed with a long immersion Marshall test 0.5 hours and 24 hours, and Indirect Tensile Strength test which is done on unconditioned and conditioned specimen. From the result, the optimum asphalt content for variation 1, 2, 3, 4, and 5, is a follows 6.0%, 6.1%, 6.15%, 6.2%, and 6.5%. The results of standard marshall test (0.5 hours of immersion) shows the stability values for variation 1, 2, 3, 4, and 5 is a follows 1591 kg, 1488 kg, 1424 kg, 1298 kg and 1295 kg. In the standard marshall test (24 hours of immersion) shows the stability value is a follows 1564 kg, 1428 kg, 1317 kg, 1285 kg and 1271 kg. The obtained index value of remaining strength (IRS) meets the requirements of Bina marga. From the results, it shows the highest IRS value in variation 4 (98.9%) and the lowest is in variation 3 (92.5%). AC-Binder Course mixture which uses Jatropha oilcake ash is less resistant to crack, this can be seen in the Tensile Strength Ratio (TSR) which is shown by variation 1, 2, 3, 4, and 5 as follows 88%, 89%, 76%, 70%, and 66%.